From an Individual to the European Integration - Discussion on the Future of Europe: Liber Amicorum in Honour of Prof. Emer. Dr. Silvo Devetak on the Occasion of his 80th Birthday (University of Maribor Press, 2019)
»From an Individual to the European Integration, Discussion on the Future of Europe - Liber Amicorum in Honour of Prof. Dr. emer. Silvo Devetak on the Occasion of his 80-ies Birthday« is a tremendous collection of articles dedicated to Prof. Dr. emer. Silvo Devetak. The nationally and internationally estimated scholars, from eleven states, have written significant articles. These estimated scholars are academics, researchers, colleagues and friends, who shared common ideas, visions, work and research (some for decades) with Professor Devetak. In their articles, which are dedicated to the wide opus of the field of interest of Professor Devetak, they discuss, argue, analyse or overview the topics especially related to public international law, human rights, minorities and EU neighbourhood policy.